Classification of food menu and grouping of food potential to support the food security and nutrition quality. (2022) - Mardianto, M. Fariz Fadillah; -, Suliyanto; Effendy, Faried; Simamora, Antonio Nikolas Manuel Bonar; Cahyasari, Ayuning Dwis; Purwoko, Chaerobby Fakhri Fauzaan; Aliffia, Netha
No abstract available